Contaminants in Foods of Animal Origin in Cameroon: A One Health Vision for Risk Management “from Farm to Fork” - Pouokam, Guy B.; Foudjo, B. U. Saha; Samuel, Chi; Yamgai, Philomina Fankam; Silapeux, A. Kamda; Sando, Joel Taguemkam; Atonde, G. Fankam; Frazzoli, Chiara (Frontiers in Public Health, 2017)
Foods of animal origin represent an important share in the diet of Cameroonian populations. Cameroon is known to be a food basket in the west and central Africa sub-region, and an important supplier of foods on the international markets. In the meantime, food importation is continuously increasing to meet the high demand of a more westernized segment of the population. Cereals, fish, sea products, eggs, honey, shrimps, chicken, and feed ingredients are important share in the international trade of agricultural products. Few controls are made on the quality and safety of these products. Certain safety standards do exist but are still yet to be enforced. Inspections done so far by regulatory authorities are partial and do not cover important hazards that require laboratory analysis. The increasing awareness of population, the burden of new types of disease, as well as the recurrence of food scandals have recently launched a scientific and population debate on the contribution of foods items, especially those of animal origin, to the toxic exposure of food producing animals and humans. This paper critically reviews the occurrence of toxicants in most consumed foods of animal origin in Cameroon. This study included the most consumed food of animal origin, identified during the national household budget survey and contributing to 8.1% of the total diet of an individual. Data evaluated suggest an important contamination by toxic metals, mycotoxins, veterinary drugs’ residues, and pesticides. The current national legal framework is briefly analyzed to explore possible intervention measures in the frame of the One Health approach.